Pilgrim Tourist Service Practices Muara Jambi Compound Temple - Dian Sari; Johannes; Raja Sharah Fatricia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the service practices of pilgrim tourists at Muarajambi Temple, a heritage-based pilgrim tourism destination. The study used a qualitative approach with a case study design to gain an in-depth understanding of the service practices applied to pilgrim tourists. Research informants were selected purposively, consisting of area managers, tourism operators, religious leaders, and pilgrim tourists. Data were collected through in-depth interviews, field observations, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that pilgrim tourist services have accommodated the basic needs of visitors by providing physical facilities, spiritual information, and assistance in carrying out religious rituals. These service practices form three main patterns: informative services, assistance services, and facilitative services. Analysis based on the 4A concept shows that the attraction is the main strength of the area because it has high historical, cultural, and spiritual value. However, aspects of accessibility, amenities, and supporting services still require strengthening, especially in service integration, provision of facilities appropriate to pilgrims' needs, and coordination between stakeholders. These findings confirm that the development of a more structured service system is an important factor in improving the quality of the tourist experience while supporting the sustainability of cultural heritage-based religious tourism